Legal Harmonization in the Distribution of Inheritance in the Dayak Ngaju Community in Central Kalimantan, Indonesia - Syaikhu, Syaikhu; Al Amruzi, M. Fahmi; Mujiburahman, Mujiburahman; Norwili, Norwili (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The study aims to seek customary law in the Dayak Ngaju community to become a solution to settlement of inheritance law. Customary law in the Indonesian legal system is one of the doors to the eclecticism of inheritance law which can be developed as part of the construction of national inheritance law, so that there is a process of harmonization and integration of the inheritance law. This research is emperical juridical research using statutory and legal pluralism approaches. The legal pluralism approach aims to examine the harmonization and integration of various legal systems applied in society. The data analyzed came from scientific documents and in-depth interviews with traditional leaders. The results of the research show that there is competition for norms, encounters or conflicts between various legal systems. Some of the reasons that can be put forward are. First, customary law as a sub-system of the customs of the Dayak Ngaju community is an unwritten law that has long existed and has become part of the legal awareness of the Dayak community itself, both in personal, family, group and community life in every activity. Second, the Dayak Ngaju customary inheritance legal system is not a system that stands alone. If the inheritance law system changes, the change will disrupt social cohesion that has been built for a long time. Efforts towards the unification and condification of inheritance laws that apply nationally should be started, in addition to avoiding family conflicts, providing legal certainty, as well as reforming things that are considered unfair in the inheritance law system. It is also a part of legal pluralism which recognizes and provides space for the development of various laws that live in society.